AB0131 Adiponectin Promotes Synovial Fibroblast Survival, Migration and Invasion in Rheumatoid Arthritis. (9th June 2015) - Lin, N.; Wei, Y.; Tan, W.; Zhang, M.
Abstract : Background: In our previous study, we found that the expression of adiponectin and adiponectin receptor 1 in synovial fluids and synovial tissues of patients with rheumatoid arthritis is higher than the normal.Furthermore, we found that adiponectin stimulate the expression of RANKL to excerbate bone ersion in rheumatoid arthritis. Objectives: To investigate whether adiponectin (AD) promotes rheumatoid arthritis synovial fibroblasts (RASFs)survival, migration and invasion. Methods: RASF was transfected with adiponectin receptor 1-siRNA (ADR1-siRNA) or (ADR2-siRNA) for 48h and then treated with AD for 24h.The proliferation, apoptosis, nigration and invasion of RASFs was analysised by CCK-8 kit, flow cytometry and transwell corning, respectively.The expression of apoptosis-related genes and cytokines was tested by Real-time PCR and western-blot. Results: The frequencies of apoptosis cells were significant decreased in RASFs after AD stimulation. AD markedly promote proliferation, migration and invasion of RASFs compared with untreated it.When knockdown AdipoR1 and AdipoR2, the effect of adiponectin on RASFs survial, migration and invasion was decreased. The expression of apoptosis-related genes CDK4 and PCNA were markedly increased but p53 mRNA was obviously decreased in RASFs after treated with AD.The level of IL-6, IL-8 and MMP-2, MMP-3 and MMP-9 expression also significantly increased in RASFs upon AD stimulation.Western blot indicated that AD could rapidly triggered p-AKT and p-ERK activity and then induced Bcl-2, MMP-2 and MMP-9, but decreased Bax expression in RASFs.When small interfering RNA knockdown AdipoR1 and AdipoR2, the Bcl-2, MMP-2, MMP-9 mRNA and protein was decreased. Conclusions: Our findings indicate that AD could promotes RASFs survival, migration and invasion via adiponectin receptors, suggesting a critical role of AD on disease progression in RA. References: McInnes IB, Schett G. The pathogenesis of rheumatoid arthritis. The N Engl J Med. 2011;365(23):2205219. Upchurch KS, Kay J. Evolution of treatment for rheumatoid arthritis.Rheumatology (Oxford). 2012;51 Suppl 6:vi28236. Cohen G, Gossec L, Dougados M, Cantagrel A, Goupille P, Daures JP, et al.Radiological damage in patients with rheumatoid arthritis on sustained remission. Ann Rheum Dis. 2007;66(3):358263. Andersen M, Boesen M, Ellegaard K, Christensen R, Soderstrom K, Soe N, et al. Synovial explant inflammatory mediator production corresponds to rheumatoid arthritis imaging hallmarks: a cross2sectional study. Arthritis Res Ther. 2014;16(3):R107. Schett G, Gravallese E. Bone erosion in rheumatoid arthritis: mechanisms, diagnosis and treatment. Nat Rev Rheumatol. 2012;8(11):656264. Versini M, Jeandel PY, Rosenthal E, Shoenfeld Y. Obesity in autoimmune diseases: Not a passive bystander. Autoimmun Rev. 2014. Peer Review Kerekes G, Nurmohamed MT, Gonzalez2Gay MA, Seres I, Paragh G, Kardos Z, et al. Rheumatoid arthritis and metabolic syndrome. Nat Rev Rheumatol. 2014. Chen X, Lu J, Bao J, Guo J, Shi J, Wang Y. Adiponectin: a biomarker for rheumatoid arthritis? Cytokine Growth Factor Rev. 2013;24(1):8329. Tan W, Wang F, Zhang M, Guo D, Zhang Q, He S. High adiponectin and adiponectin receptor 1 expression in synovial fluids and synovial tissues of patients with rheumatoid arthritis. Semin Arthritis Rheum.2009;38(6):42027. Acknowledgements: We thank the technical support from Department of Cardiology, The First Affiliated Hospital of Nanjing Medical University. Disclosure of Interest: None declared